Penyuluhan Dan Servis Sepeda Motor Gratis Di Desa Kenalan Kec. Borobudur, Kabupaten Magelang - Aryananta Lufti; Budi Harijanto; Sukahar; Muhammad Zainuddin (PPM Sdirjianbang Akademi Militer, 2026)
This community service activity conducted by the Defense Mechanical Engineering Study Program of the Military Academy aimed to improve public awareness of motorcycle maintenance and to provide free motorcycle service to the community. The activity was implemented through two main components, namely motorcycle maintenance counseling and periodic motorcycle servicing. The implementation ran smoothly and systematically in accordance with the planned schedule, supported by the readiness of the implementation team and adequate technical equipment. The results indicated that the target was successfully achieved, with a total of 70 motorcycles receiving free service. Furthermore, the level of community enthusiasm was very high, as reflected in the strong participation of residents, active involvement during the counseling sessions, and utilization of vehicle maintenance consultations. This activity provided direct benefits to the community by ensuring safer and more reliable motorcycle conditions, while also strengthening the role of higher education institutions in fulfilling the Tri Dharma of Higher Education, particularly in community service.